Dominance hierarchy regulates social behavior during spatial movement - Lara-Vasquez, Ariel; Espinosa, Nelson; Morales, Cristian; Moran, Constanza; Billeke, Pablo; Gallagher, Joseph; Strohl, Joshua J.; Huerta, Patricio T.; Fuentealba, Pablo (Frontiers in Neuroscience, 2024)
The authors propose a very intriguing relationship between dominance hierarchy and social interaction on spatial navigation. However, the data do not seem to fully support the authors' bold claims, according to this reviewer's opinion.Generally, given the fickle nature of LFP amplitude recordings, one would generally assume that a large number of animals per group (say n=8-10) would be necessary to support such findings. There are a number of purely statistical issues with the manuscript, as described:1. The authors state that n=15 cages of 4 animals each were used. However, the figures seem to only report use of n=21 mice for recordings. Please clarify how the animals were chosen for